Принципи права в контексті розвитку загальної теорії держави і права - Зайчук, О.В. (Альманах права, 2012)
У статті розглядаються правові принципи, які пронизують правову матерію, і у першу чергу, правові ідеї. Принципи — це передусім ідеї. Елемент узагальнення, піднесений над конкретикою, властивий ідеї, досить чітко простежується і в принципах права. Потім принципи перетворюються у норми, втілюються у них. Закон можна вважати правовим настільки, наскільки він уособлює демократичні правові принципи. І насамкінець, зазначає автор, принципи права пронизують процес реалізації права. Вони концентрують результат розвитку права, в них втілюється нерозривний зв’язок минулого, сучасного та майбутнього. В статье рассматриваются правовые принципы, которые пронизывают правовую материю, и в первую очередь, правовые идеи. Принципы — это прежде всего идеи. Элемент обобщения, возвышенный над конкретикой, присущий идее, достаточно четко прослеживается и в принципах права. Потом принципы превращаются в нормы, воплощаются в них. Закон можно считать правовым настолько, насколько он олицетворяет демократические правовые принципы. И в конце, отмечает автор, принципы права пронизывают процесс реализации права. Они концентрируют результат развития права, в них воплощается неразрывная связь прошлого, настоящего и будущего. The article is examined legal principles and legal ideas. Principles are the ideas but not only. Principle is engendered as a certain idea in a theory, fastened in the system of legal norms and through them grows into public relations or vice versa: public relations concentrated and fastened in the norms of law and are their basis. Thus, the chart of realization, transformation, in life of principles coincides with the mechanism of origin and realization of right. There are two principal scientific items, in particular: legislative fixing of legal principle (ideas which are not fastened in a law can not be considered as legal principles); regulative influence on law-enforcement practice can do such legal ideas-principles which are not fastened in law. An author marks that public interests and necessities which are formed and change regardless of legislator will are fixed in basis of principle. In particular, a basic role in the exposure of such necessities belongs to legal practice which reacts onto changing of place in the field of law.